2005
DOI: 10.1111/j.0105-1873.2005.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch test reactions to cosmetic allergens in 1995–1997 and 2000–2002 in Finland – a multicentre study

Abstract: Contact sensitivity to cosmetics is common, but the sensitizing chemicals vary between countries and study periods. The present survey aimed at revealing the recent trends in patch test sensitivity with cosmetic chemicals in Finland. We report a retrospective multicentre survey of patch test reactions focusing on cosmetic-related substances and comparing the test results in 1995-97 with those in 2000-02. The most striking increases in the frequency of the patch test sensitivity were found with balsam of Peru a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 27 publications
6
50
0
7
Order By: Relevance
“…In a Finnish study of patch-test reactions to cosmetic allergens, diazolidinyl urea was responsible for only 0.9% of allergic reactions in 6539 patients. 32 In contrast, we found that diazolidinyl urea represented 2.7% (both aqueous and petrolatum preparations) of reactions in females and 4.9% (aqueous) and 5.6% (petrolatum) of reactions in males to cosmetic products and was commonly implicated in the following sources: cosmetics NOS, moisturizers, and make-up formulations.…”
Section: Formaldehyde-releasing Preservativesmentioning
confidence: 72%
“…In a Finnish study of patch-test reactions to cosmetic allergens, diazolidinyl urea was responsible for only 0.9% of allergic reactions in 6539 patients. 32 In contrast, we found that diazolidinyl urea represented 2.7% (both aqueous and petrolatum preparations) of reactions in females and 4.9% (aqueous) and 5.6% (petrolatum) of reactions in males to cosmetic products and was commonly implicated in the following sources: cosmetics NOS, moisturizers, and make-up formulations.…”
Section: Formaldehyde-releasing Preservativesmentioning
confidence: 72%
“…It is often added to a variety of cosmetics including lip products (lipsticks, lip balms), moisturizers, powders, shaving creams, shampoos, and soaps, and it may be a source of allergy from cosmetic products. 105,106 Ointment bases for topical medicaments are another common source of lanolin exposure.…”
Section: Vehicles Emulsifiers and Surfactantsmentioning
confidence: 99%
“…The vehicles, humectants, emollient, and emulsifier may also work as an antigen [29][30][31][32] . From the ingredients that are frequently used as the cosmetic product ingredient and may cause the ACD, the ingredients that are not included to the cosmetic series are petrolatum 30 , glycerin 33 , glycol (butylenes glycol, polyethylene glycol, pentylene glycol, hexylene glycol) 33,34 , lanolin 35 , castor oil 36,37 , propolis (bee-glue) 38,39 and others. Glycerin may rarely induce sensitization 33 .…”
Section: Discussionmentioning
confidence: 99%